Cultural Dynamics Revealed: Aesthetic Exploration of Symbols and Meanings in the Design of the Nine Gates of Astana Sunan Gunung Jati Cirebon - Santosa, Imam; Hendryana, Husein (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
Astana Sunan Gunung Jati is a royal burial complex and religious leadership site located in Cirebon, West Java-Indonesia, representing a unique model of acculturation and adaptation from diverse cultures and traditions. This research aims to examine a masterpiece of 14th-century architecture to understand the adaptation processes involved in its construction and uncover the aesthetic contributions from various sources to the design of Astana Sunan Gunung Jati. The primary challenge lies in harmoniously integrating diverse cultural elements and the influences of various religions that shape its design and aesthetics. This study focuses on the representation of different cultural elements interacting and contributing to the Islamic cultural richness in Cirebon, particularly in the visualization of the nine symbolic gates of Astana Sunan Gunung Jati. Employing a qualitative approach, the research delves into cultural adaptation into visual forms, utilizing historical data, literature, and in-depth interviews with relevant parties knowledgeable about Astana Sunan Gunung Jati. The findings reveal that the design of Astana Sunan Gunung Jati adopts a pluralistic and multicultural approach, blending models of 'native cultural preservation' and 'cultural contact synergy'. This reflects the cultural convergence from sources including Sundanese, Javanese, Islamic, Buddhist, and Hindu traditions, contributing to the visual richness of the structure. Moreover, this research significantly shapes the cultural identity of Cirebon. The cultural adaptation process in the design of Astana Sunan Gunung Jati, which has endured for approximately 700 years, holds profound insights into the aspects of maintenance, preservation, and conservation, serving as a role model for cultural heritage. It offers valuable insights into how cultural identity forms and is preserved in complex and diverse environments, particularly concerning design and aesthetics.